СПОРТ ТАРАЎЫНДАҒЫ МАРКЕТИНГТИҢ АЙЫРЫМ ӨЗГЕШЕЛИКЛЕРИ - Қалжанов, П.У.; Тойлибаев, С.М.; Кеңесбаева, Д.Б. (FAN va JAMIYAT, 2017)
Marketing today is an important complementary part of the development of physical culture and sport in general. Relationship of marketing and sports gives more opportunities for the development of both an individual athlete and sport clubs in general.